Study of oxidative stress biomarkers in obese children - Fariya, Avni Kanji; Dias, Bina F. (International Journal of Research in Medical Sciences, 2018)
Background: The objective is to study the oxidative stress in obese and non-obese children by assessing the biomarkers of lipid peroxidation and antioxidant status, Malondialdehyde (MDA) and Ascorbic acid (vitamin C) respectively. Childhood obesity is a growing global epidemic that requires attention due to the burden placed on the healthcare system for children and adults. Consumption of fatty foods and a high sugar, fat diet, and no exercise qualify as the main reasons for obesity among children and adults. Childhood obesity is connected with an increased risk of various diseases such as diabetes, cardiovascular, stroke, certain types of cancer later in life, social problems and depression among youths. Obesity is also characterized by chronic low grade inflammation with permanently increased oxidative stress (OS). Over-expression of oxidative stress damages cellular structures together with under-production of anti-oxidant mechanisms, leading to the development of obesity-related complications. Methods: The study involved 25 obese children for Vitamin C, 20 obese children for Malondialdehyde (MDA) and 18 non obese children for both Vitamin C and MDA in the age group of 5-14 years, without any complications. This study was conducted at L.T.M.M College. Plasma Ascorbic Acid was estimated colorimetrically by using 2,6- dicholrophenol indophenol dye and similarly Malondialdehyde was estimated colorimetrically by MDA-TBA colored complex. Results: The study showed significantly higher values of MDA and lower level of Vitamin C in obese children as compared with non-obese children. Conclusions: The levels of lipid peroxidation marker Malondialdehyde (MDA) is higher and level of antioxidant marker Ascorbic Acid (Vitamin C) is lower in obese children as compared with non-obese children. Thereby increasing oxidative stress and hence the oxidative damage to cells.